Expanded Yet Restricted: A Mini Review of the Soft Skills Literature - Touloumakos, Anna K. (Frontiers in Psychology, 2020)
There has been a progressively heightened preoccupation with soft skills among education stakehold-ers such as policymakers, educational psychologists and researchers. Soft skill curricula have been considered these days -and developed not only for graduates and as on-the-job training programmes, but also for students across all levels of education. However, different people mean different things when referring to soft skills. This review presents evidence to suggest that the use of the term ‘soft skills’ has expanded to encompass a variety of qualities, traits, values and attributes, as well as rather distinct constructs such as emotional labour and lookism. It is argued here that these infinite catego-ries of things that can be skills because soft skills research is primarily focused on what are the needs and requirements in the world of work. This approach is problematic because it assigns characteristics to soft skills which in turn affect the design of the soft skills curricula. For example, soft skills are often construed as de-contextualized behaviours which can be acquired and transferred unproblemati-cally. The paper proposes that an in-depth and embedded approach to studying soft skills should be pursued to reach a consensus on what they are and how to develop them because otherwise they will always be expanded before restricted (as they have become ambiguous) in their meaning and defini-tion.